2021
DOI: 10.6004/jnccn.2020.7668
|View full text |Cite
|
Sign up to set email alerts
|

Bone Metastases, Skeletal-Related Events, and Survival in Patients With Metastatic Non–Small Cell Lung Cancer Treated With Immune Checkpoint Inhibitors

Abstract: Background: Bone metastases and skeletal-related events (SREs) are a frequent cause of morbidity in patients with metastatic non–small cell lung cancer (mNSCLC). Data are limited on bone metastases and SREs in patients with mNSCLC treated using immune checkpoint inhibitors (ICIs), and on the efficacy of bone-modifying agents (BMAs) in this setting. Here we report the incidence, impact on survival, risk factors for bone metastases and SREs, and impact of BMAs in patients with mNSCLC treated with ICIs in a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Subsequently, denosumab has become the most commonly used BMA in Taiwan. Despite this, not all NSCLC physicians prescribe BMAs to manage bone diseases or SREs [ 21 , 22 , 23 , 24 , 25 ]. In addition, physicians and/or patients often decide to initiate bone treatment upon the occurrence of SREs or later in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, denosumab has become the most commonly used BMA in Taiwan. Despite this, not all NSCLC physicians prescribe BMAs to manage bone diseases or SREs [ 21 , 22 , 23 , 24 , 25 ]. In addition, physicians and/or patients often decide to initiate bone treatment upon the occurrence of SREs or later in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is that the therapeutic effect of denosumab involves SREs reduction, which may prevent an exacerbation of the performance status and prolong survival. However, two recent analyses failed to show the advantage of denosumab in NSCLC patients receiving chemotherapies and immunotherapies [ 4 , 22 ]. This evidence prompted us to examine whether denosumab has beneficial effects in certain NSCLC subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the tumor and bone microenvironment play an important role. Several studies [ 6 , 13 , 14 , 15 ] suggest that bone involvement may be a negative prognostic factor and the presence of BoM could be predictive of a poor response to ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…Bone involvement has been associated with poor survival either with platinum-based chemotherapy or immunotherapy in NSCLC patients (Qin et al 2021;Tournoy et al 2018;Landi et al 2019).…”
Section: Introductionmentioning
confidence: 99%